Crescimento, desenvolvimento, dimensionamento amostral e atividade antiproliferativa de calêndula - Padilha, Pedro Hernandez (2016)
Calendula is an important plant cultivated in southern Brazil with medicinal properties, therapeutic and for increasing farmers' income. The goals of the study were to estimate the morphological characters like flower height (cm), plant height (cm), number of leaves per plant and diameter of the flower head (cm) of the main stem, also the productive characters as dry mass (g plant-1) and seed mass (g plant-1); ascertain the viability of seed production for the species, the duration of growth periods and development in growing seasons; determine sample sizes for average estimation of the characters mentioned above, with the exception of the seed mass; check the variability of the sample sizes between the characters and evaluation periods and; evaluate the genotoxic and anti-proliferative effects of calendula infusions on the in vivo test system of Allium cepa. It was conducted a field experiment in a randomized block design with three factors which are: growing seasons (August/14, October/14 and April/15), cultivars (Bonina Dobrada Sortida and Bon Bon Yellow) and cropping systems (direct seeding and transplanting seedlings), in a total of twelve treatments. The results indicate greater cycle, flowering period and growth to the period April/15. Cultivar Sortida was superior than Yellow for any combination of seasons and cropping systems for flower height character ranging between 26.84 cm to 39.76 cm. Plants originated by direct seeding demonstrated superiority for flower height for season April/15, regardless of the cultivar. This system was also higher for characters like plant height, leaf number, and dry mass and mass of seeds at the time April/15. For plant height, leaf number and dry weight of the plant growing seasons in August/14 October/14 and April/15 the variety Sortida had the highest averages. In relation to growing seasons, the flower head diameter character had the highest average in the period April/15 of 6.82 cm. Among the cultivars, Sortida differed from variety Yellow by showing 7.03 cm average. The germination percentages of the seeds harvested in three seasons under study were very low for use by the producer. Sample sizes were very different between the characters, and for plant height and number of leaves values were similar in the evaluation performed soon after transplanting and flowering plants. There were necessary smaller sample sizes for morphological characteristics in relation to dry mass production. Evaluation of 190 plants is enough to estimate the mean amplitude of the parameters evaluated for a 95% confidence interval with a maximum error of 20% of the mean estimate. Infusions derived from cut flowers of the season in August/14 showed antiproliferative effect, reducing the mitotic index compared to controls for all infusions, it is not possible to determine whether there are genotoxic effects.